2015
DOI: 10.1002/14651858.cd010663.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus non-surgical interventions in people with adolescent idiopathic scoliosis

Abstract: Bunge 2007 {published data only} Bunge EM, Juttmann RE, De Kleuver M, Van Biezen FC, De Koning HJ. Health-related quality of life in patients with adolescent idiopathic scoliosis after treatment: shortterm effects after brace or surgical treatment. European

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 54 publications
1
84
0
1
Order By: Relevance
“…There is a growing body of evidence concluding that surgery is rarely necessary for AIS [24252652] and that it is usually done for cosmetic and psychological purposes. Based on the current literature, Westrick and Ward [25] concluded that there is no medical necessity for surgery for AIS; this conclusion was recently confirmed by the results of a Cochrane review [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of evidence concluding that surgery is rarely necessary for AIS [24252652] and that it is usually done for cosmetic and psychological purposes. Based on the current literature, Westrick and Ward [25] concluded that there is no medical necessity for surgery for AIS; this conclusion was recently confirmed by the results of a Cochrane review [26].…”
Section: Discussionmentioning
confidence: 99%
“…This is applicable to AIS patients with curve magnitudes of ≥40° with a potential for further growth and for those with curve magnitudes of ≥50° at or near skeletal maturity. This is standard practice, although there is a clear absence of high-level evidence for recommendation of spinal fusion surgery [2223242526]. Therefore, the indications for surgery need to be reevaluated based on the natural long-term effects of patients with AIS (the most prevalent population).…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane review carried out in 2015 found that no conclusion could be drawn from the literature with regard to surgical versus non-surgical interventions in severe AIS; this study was an ''empty review'' which nonetheless highlighted the alarming dearth of research in this field. 3 Likewise, an earlier review found no evidence that the health-related aspects of AIS can be altered in any significant way by surgical intervention, concluding that there is no medical justification for an intervention which is associated with a high rate of complications. scoliosis is not associated significantly with any physical impairment, other than shortness of breath and moderate back pain.…”
Section: Introductionmentioning
confidence: 99%
“…2 However at this time there is no clear consensus as to whether a minimally invasive approach is preferable to the open approach in terms of overall curve correction. Considering that there is also little evidence supporting the use of surgical techniques in the treatment of AIS when compared to less invasive techniques such as exercise or bracing, 3 these data call attention to the need for further research in this field far more eloquently than they support a particular intervention. When recommending interventions to their patients, physicians are not always guided by the best evidence, particularly when no such evidence exists; this phenomenon becomes especially clear when we consider the case of adolescent idiopathic scoliosis (AIS).…”
Section: Introductionmentioning
confidence: 99%
“…These results have demonstrated the importance of intervention for further prevention of scoliosis progression. A study by Bettany-Saltikov et al compared conservative to surgical treatment of scoliosis and found no proof of preference of one way of treatment above the other one [10] . However, a systematic review by Yadla et al showed that surgical intervention has better radiographic and clinical outcomes for the patients [11] .…”
Section: Introductionmentioning
confidence: 99%